Reconciling animal and human data in a cancer risk assessment of acrylonitrile - Schulz, Mark R; Hertz-Picciotto, Irva; Todd, Lori; Ball, Louise M (Scandinavian Journal of Work, Environment & Health, 2001)
' ' OBJECTIVES ': 'Bioassays of rats exposed to acrylonitrile have consistently detected an elevated incidence of central nervous system (CNS) cancer. In contrast, epidemiologic studies have not found a statistically stable increase in CNS cancer mortality. The purpose of this paper is to examine whether or not CNS cancers predicted from the most appropriate inhalation bioassay in rats are consistent with CNS cancers observed in 3 recent, large epidemiologic studies. ' ' METHODS ': 'A linearized multistage model was fit to dose-response data from a rat inhalation bioassay to estimate carcinogenic potency. This potency was applied to epidemiologic studies of acrylonitrile-exposed workers. After adjustment for less than complete lifetime follow-up in the epidemiologic studies, consistency was examined between CNS cancers predicted by the model fit to the animal data for the exposure levels and sample sizes of the epidemiologicy studies and the CNS cancers observed in the epidemiologic studies. ' ' RESULTS ': 'The model predicted totals of 17.7, 3.6, and 7.6 CNS cancer deaths for the studies. These predictions were not far from the observed CNS cancer deaths (12, 6, and 6) and were well within their 95% confidence intervals of 6.9-22.3, 2.2-13.1, and 2.2-13.1, respectively. ' ' CONCLUSIONS ': 'The CNS cancer potency estimated from the best available inhalation bioassay was consistent with the observed deaths in the epidemiologic studies as long as continuous lifetime exposure was chosen as the exposure metric. The lack of observed excess in CNS cancer among the studied workers may have been due to low exposures, insufficient follow-up times, or both.
Keywords: acrylonitrile; animal data; bioassays; cancer risk assessment; carcinogenic potency; central nervous system cancer; epidemiologic study; follow-up time; human data; interspecies comparison